2020
DOI: 10.1186/s12885-020-07063-1
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-lymphocyte ratio associated with poor prognosis in oral cancer: a retrospective study

Abstract: Background: Prognostic biomarkers provide essential information about a patient's overall outcome. However, existing biomarkers are limited in terms of either sample collection, such as requiring tissue specimens, or the process, such as prolonged time for analysis. In view of the need for convenient and non-invasive prognostic biomarkers for oral cancer, we aimed to investigate the prognostic values of neutrophil-to-lymphocyte ratio, lymphocyte-to-monocyte ratio, and platelet-to-lymphocyte ratio in patient su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 34 publications
3
29
1
4
Order By: Relevance
“…NLR is accepted as an effective and simple parameter of inflammation [13]. Starting from this point of view, NLR and prognosis association has been investigated in different types of cancer [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…NLR is accepted as an effective and simple parameter of inflammation [13]. Starting from this point of view, NLR and prognosis association has been investigated in different types of cancer [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Higher neutrophil levels can upregulate the expression of growth factors, such as chemokines, which play an important role in tumor development and progression. The reduction in lymphocytes indicates that the body's immunity is reduced and its antitumor ability is weakened.An increased NLR indicates that the body's in ammatory response is increased, while the lymphocyte-mediated antitumor response is decreased, which can easily cause tumor deterioration and metastasis, ultimately leading to the poor prognosis of patients 15,16,17,23,24 .Takumi Hasegawa et al reported that the NLR increased with the number of pathological lymph node metastases and shorter OS in patients with oral cancer, which was also an indication of a decrease in the lymphocyte count 25 . The results of a meta-analysis suggested that an elevated pretreatment NLR is a negative prognostic factor in patients with head and neck cancer 26 .…”
Section: Discussionmentioning
confidence: 99%
“…[29] Pada 16 artikel yang diteliti, sebanyak 11 artikel mengekslusikan faktor lain selain kanker yang dapat menyebabkan perubahan RNL seperti penyakit kronis lain dan autoimun. [12], [19]- [22], [24], [25], [27], [28], [30], [31] RNL digunakan sebagai penanda inflamasi sistemik memiliki nilai prognostik pada berbagai jenis kanker seperti kanker paru, hati, esofagus, gastric, kolorektal, dan pankreas. [12] Pada pasien kanker rongga mulut, nilai RNL yang meningkat berhubungan secara signifikan dengan penurunan overall survival (OS) dan dapat digunakan sebagai faktor prediktif untuk prognosis.…”
Section: Metode Penelitianunclassified
“…[12], [32], [35], [36] Artikel pada penelitian ini juga membahas mengenai hubungan nilai RNL dengan terjadinya metastasis ke nodus limfe atau klasifikasi N. RNL dapat menjadi faktor prediktif untuk delayed lymph nodes metastasis dan multiple lymph nodes metastasis dan nilai RNL yang tinggi diatas cut-off value dapat mengindikasikan terjadinya metastasis nodus limfe. [22], [34], [37] Penelitian yang meneliti perbedaan rata-rata nilai RNL pada pasien pN0 dan pN+, menyebutkan pasien pN+ memiliki rata-rata nilai RNL yang lebih tinggi dan nilai RNL 2.93 berkaitan dengan probabilitas terjadinya metastatis tersembunyi pada pasien cN0 [24]. Peningkatan nilai RNL sejalan dengan peningkatan histologic grading menuju moderate-poor differentiation menurut klasifikasi WHO.…”
Section: Metode Penelitianunclassified